Neutrophil Percentage-to-Albumin Ratio in the Diagnosis of Ovarian Torsion-Predictive Role - Rifat Sener; Sitki Ozbilgec; Fatih Akkus; Elif Ceyda Serin; Oguzhan Günenc (Clinical and Experimental Obstetrics & Gynecology)
Background: Ovarian torsion is a medical emergency caused by ovarian rotation and requires prompt diagnosis and treatment to prevent complications such as ovarian necrosis. In our study, we aimed to predict ovarian torsion by evaluating preoperative neutrophil percentage-to-albumin ratio (NPAR) and inflammatory parameters among patients with ovarian cyst and ovarian torsion. Methods: This retrospective study includes 167 patients who underwent surgery for ovarian cysts or ovarian torsion between January 2021 and May 2024 at Konya City Hospital. Clinical characteristics, along with preoperative hematologic and inflammatory parameters, were compared between patients with and without torsion. Results: There was no significant difference in ovarian cyst size or cyst lateralization between the ovarian cyst and ovarian torsion groups (p = 0.595 and p = 0.932, respectively). Neutrophil percentage, neutrophil count, white blood cell (WBC) count, NPAR, and neutrophil-to-lymphocyte ratio (NLR) were higher in the ovarian torsion group (n = 83) compared to the ovarian cyst group (n = 84) (all p < 0.01). Lymphocyte count was lower in the ovarian torsion group. Although the systemic immune-inflammation index (SII) was higher in the torsion group, the difference was not statistically significant. A correlation analysis was performed between patient age, ovarian cyst size, and inflammatory parameters in the ovarian torsion group. When the NPAR cut-off was set at 1.66, high sensitivity (80.7%) and specificity (95.2%) were observed for ovarian torsion. The positive predictive value (PPV) was 94.3%, and the negative predictive value (NPV) was 83.3%. The area under the curve (AUC) for NPAR was 0.892 (95% confidence interval (CI): 0.837–0.947), indicating strong predictive performance (p = 0.001). Conclusions: The higher levels of NPAR, NLR, WBC count, neutrophil percentage, and neutrophil count observed in ovarian torsion cases suggest that these parameters may be useful in diagnosing ovarian torsion. In addition, the high sensitivity and specificity values of NPAR highlights its potential for future studies in the diagnosis of ovarian torsion.